New Models of Care for Patients with Severe Mental Illness - Bridging In- and Outpatients - Alexandre Wullschleger (Frontiers Research Topics, 2018)
Over the past years, psychiatric services have been continuously faced with the challenge of providing comprehensive care to people suffering from severe mental illnesses. Legal and conceptual advances like the UN convention on the rights of persons with disabilities or the concept of recovery have rendered this challenge more actual and urgent than ever. However, psychiatric institutions often show only low levels of cooperation and integration between their different services. Hence, they need to develop new ways of bridging all sectors of care in order to help people most in need on their way to recovery and full inclusion in society. In this research topic, European researchers and clinicians present new ways of dealing with this essential issue by developing strategies and interventions on both institutional and non-institutional levels. The nine contributions of this ebook thus reflect actual clinical and conceptual considerations. They all aim at improving quality of care and providing adequate support to people suffering from severe mental illness.